Effectiveness of Vitamin D Supplementation in Children with Attention-Deficit/Hyperactivity Disorder: A Systematic Review - Okta Puspita; Made Laksmi Meiliana; Denny Ardhianto; Syaripah Ulandari (SOCIAL CLINICAL PHARMACY INDONESIA JOURNAL, 2026)
Attention-deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disorder that significantly affects functioning and quality of life. Emerging evidence suggests that vitamin D may contribute to neurodevelopment and behavioral regulation, and children with ADHD have been reported to exhibit lower serum 25(OH)D concentrations. However, findings regarding the clinical effectiveness of vitamin D supplementation remain inconsistent. This study systematically reviewed the effectiveness of vitamin D supplementation in children with ADHD. A systematic review was conducted in accordance with PRISMA guidelines by searching PubMed, ScienceDirect, and Scopus for randomized controlled trials (RCTs) published between January 2016 and February 2026. Eligible studies included children aged ≤18 years diagnosed with ADHD who received oral vitamin D supplementation. Study quality was assessed using the Joanna Briggs Institute Critical Appraisal Checklist, and a qualitative synthesis was performed. Six RCTs met the inclusion criteria. Across studies, vitamin D supplementation consistently increased serum 25(OH)D concentrations. However, clinical effects were heterogeneous. Although some trials reported modest improvements in specific symptom domains, particularly inattention, consistent reductions in overall ADHD severity were not observed. In conclusion, vitamin D supplementation effectively improves serum 25(OH)D levels but demonstrates variable clinical benefits in children with ADHD. Current evidence does not support its use as a definitive standalone treatment, although potential adjunctive benefits cannot be excluded. Further high-quality, large-scale RCTs are needed to clarify its clinical role.